Modal Ventura Dan Perkembangan UKM Yang Listing di Bursa Efek Indonesia - Myrna Sofia; Kiki Wulandari; Firwan Tan; Nasri Bachtiar; Febriandi Prima Putra; Muhammad Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2022)
The purpose of this study is to find out and analyze SMEs that have successfully listed on the IDX and are backed up by venture capital companies in the period 2019 to 2021. Using the quantitative descriptive method, it was obtained that in 2020 one startup company that was successfully listed on the Indonesia Stock Exchange using an Acceleration board and backed up by venture capital, namely PT. Cashlez Worldwide Indonesia (CASH) with Mandiri Capital Indonesia as a venture capital company which is a subsidiary of Bank Mandiri Indonesia. The CASH company experienced a very significant development when viewed from changes in the number of assets, revenue, labor and profitability in the period before, during and after the IPO.